The Influence of Traditional Game Engklek on the Development of Numeracy Literacy in Batam Early Childhood Education Institutions - Imamah Imamah; Maelawati Suhardja (Journal of Childhood Development, 2024)
This research was conducted to significantly compare the ability to recognize numeracy literacy in children, between the group that learned with the traditional engklek game and the group that did not use engklek game, in group B at RA Miftahul Jannah Batam City during the 2023-2024 school year. Research Methods this is quantitative with an experimental approach. The population of this study was all group B children at RA Miftahul Jannah, Batam City, totaling 26 students. The sample was determined using random sampling. The sample in this study was group B1 children, totaling 13 children as the experiment group whose learning used the traditional game of engklek, and group B2 children totaling 13 children as the Kontrol group with conventional learning. Data on children's abilities in numeracy literacy were collected using observation techniques. Data reduction, data presentation and conclusion drawing are carried out in data analysis. Based on the research results, it is revealed that there is a significant influence of the traditional engklek game on the development of numeracy literacy in group B children at RA Miftahul Jannah, Batam City, which can be seen from group B1 children who learn using the traditional engklek game more quickly grasping the development of numeracy literacy compared to group B1 children. B2 who do conventional learning